Cognitive ability, financial literacy, and narrow bracketing in time-preference elicitation - Luis Oberrauch; Tim Kaiser (ZBW - Leibniz Information Centre for Economics, 2021)
We study the role of cognitive ability and financial literacy for inter-temporal decision-making using an adapted version of the Convex Time Budget Protocol. We document substantial heterogeneity in choice-patterns and estimated parameters at the individual-level: We find that subjects with higher cognitive ability and domain specific-knowledge are more likely to make patient inter-temporal choices, to allocate the entire budget to a single payment-date, and to allocate the entire budget to corner choices as interest rates increase. At the same time, domain specific knowledge is uncorrelated with choice consistency and estimated individual error parameters, suggesting these results are not driven by a reduction in random noise among high ability respondents. These results serve as suggestive evidence for inter-temporal arbitrage among high ability respondents, thereby revealing a potential confound in time-preference elicitation tasks relying on time-dated monetary rewards.
Keywords: G53; D15; D91; 330; Intertemporal choice; cognitive ability; financial literacy; narrow bracketing; arbitrage